The Flu Film as a Medium for Creative and Innovative Solutions to Directly Inform the Response to the Current Covid-19 Outbreak in Humanitarian Settings - Azhari (Winaya Inspirasi Nusantara Foundation, 2021)
Purpose: This theoretical article is intended for complex analysis of complicated phenomena and processes of the promotion of creativity and creative changes in the main areas of the contemporary social and economic life. To reduce the spread of the virus around the world is by way of humanitarian arrangements. Films are one of the media capable of influencing human behavior because films are not only entertainment but also mass communication media capable of influencing human emotions. Methods: This research is descriptive qualitative, describes, and analyzes events or a phoneme. Researchers use interaction theory and the theory of stimulus - organism - response (SOR). The data collection techniques of this research were interviews and visual documentation. The informants were those who had watched the film The Flu. Results: Based on the data obtained from the informants and the symbol analysis found that with the film The Flu is able to influence and set human behavior in pandemic conditions, especially in dealing with the Covid-19. Conclusion: Based on the results of the study showed that the film The Flu had as succeeded in increasing the awareness and seriousness of many people in stopping this pandemic, to setting up behavior to be more alert, vigilant, obeying all the gifts from health organizations and the government, one of which is aware of social distancing and physical distancing in daily activities.